Features of Legal Regulation of the Procedure for the Consideration of Labor Disputes in Kazakhstan - ISSAYEVA, Ainur Zhenisovna; AITIMOV, Bolat Zholdasbekovich; ISSAYEVA, Zhanat Amandykovna; ZHUSSUPBEKOVA, Madina Koishibayevna; TINISTANOVA, Saltanat Saidakhmetovna; MADALIYEVA, Akzada Alaidarkyzy (Journal of Advanced Research in Law and Economics, 2020)
This study examined the experience of Kazakhstan, which created its own system of laws and regulations in the field of labor dispute problems, designed to protect the interests of workers and help ensure a minimum level for residents. The article identifies problems requiring study of issues on the application of labor legislation, development of recommendations for improving and taking measures to inform judicial practice in this category of cases. We have studied the activities of the International Labor Organization (hereinafter referred to as the MOT), which is the world agency of the United Labor Organization. Kazakhstan reports on labor issues, labor disputes, trade unions of workers, workers and others. Case studies show labor disputes, strikes by workers in the regions of Kazakhstan, as well as their solutions. The study makes recommendations of the following nature, when considering disputes regarding the recognition of  legal relations as labor, courts should distinguish between civil law relations and labor relations. The relevance of the research topic due to the need to develop and introduce new modern mechanism for resolving individual labor disputes, including pre-trial and non-judicial methods of conflict resolutions.